Wannakam bai sīamsī nai Nakh̨̄on Sī Thammarāt : kānsưksā ch̄œng wikhr̨o - Wimon Damsī (Chut Nakh̨̄on Sī Thammarāt khadīsưksā (Sathāban Rātchaphat Nakh̨̄on Sī Thammarāt. Samnak Sinlapa læ Watthanatham) ;, 1998)
Study on fortune telling by numbers, a part of Chinese astrology practiced in Nakhon Si Thammarat Province, Thailand.